Քսուքի և օծանելիքի պատրաստման հին հայկական դեղագիրը Քսենոֆոնի «Անաբասիս» երկում - Վարդանյան, Ստելլա (Մատենադարան)
В состав древнего армянского рецепта приготовления мази и благовония из “Анабасисa” древнегреческого ученого Ксенофонта (V-IVвв. до н.э.) входили четыре компонента: свиное сало, масло кунжута, горький миндаль, имеющие специфические лекарственные и косметические свойства. Те же компоненты применялись в средневековой армянской медицине, по данным энциклопедии лекарственных средств – книги выдающегося врача XV века Амирдовлата Амасиаци “Ненужное для неучей” (1478-1482). The ancient Armenian recipe for preparing ointment and incense from the Anabasis by the ancient Greek historian Xenophon (5th-4th cc. BC) included four ingredients: lard, sesame oil, bitter almonds and gum of turpentine tree, which have specific medicinal and cosmetic properties. The same components were used in medieval Armenian medicine, as witnessed by the medical encyclopedia: the book Useless for the Ignorants (1478–1482) of the outstanding 15th c. physician Amirdovlat‘ Amasiats‘i.
Keywords: Բնագիտություն